2008
DOI: 10.1037/0278-6133.27.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of physical activity behavior change: A multivariate approach.

Abstract: Using a multivariate extension of the Baron and Kenny (1986) mediation framework, we examined the simultaneous effect of psychosocial variables hypothesized to mediate the relationship between a motivationally-tailored physical activity intervention, and 6-month physical activity behavior in 239 healthy, under-active adults (mean age=47.5; 82% women). Participants were randomly assigned to 1) Print-based feedback; 2) Telephone-based feedback; or 3) Contact Control. All mediation criteria were satisfied for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
96
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 55 publications
11
96
1
2
Order By: Relevance
“…Three constructs are hypothesized to mediate the change process: decisional balance, cognitive and behavioral processes of change, and self-efficacy [10]. A number of studies have examined theoretical constructs from the TTM as mediators of PA change, and findings have been mixed [5,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Three constructs are hypothesized to mediate the change process: decisional balance, cognitive and behavioral processes of change, and self-efficacy [10]. A number of studies have examined theoretical constructs from the TTM as mediators of PA change, and findings have been mixed [5,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] Whether enhancement of sociopsychological factors influences health behaviors is uncertain. 12,13,19,[22][23][24][25][26][27][28][29][30][31][32] Among trials comparing patients receiving sociopsychologically tailored colorectal cancer screening interventions with active control, 15,19,20,22,[25][26][27][28][29][30]33 only some found superior effects of tailoring 19,25,28,29,34 ; in all but 1 trial 34 screening was self-reported, 19,25,28,29 suggesting possible response bias. There is a need to examine further whether objectively measured colorectal cancer screening improves in response to sociopsychologi...…”
Section: Introductionmentioning
confidence: 99%
“…57 Nonetheless, these EHBM factor effect sizes are comparable to those in published trials. [10][11][12][13][14][15][16][17][18][19][20][21][22] In our sample, a 1 SD increase in self-efficacy was associated with a 5.4% greater likelihood of screening (data not shown, available upon request). Thus, the IMCP self-efficacy effect size of 0.16 would be expected to translate into a less than 1% increase in screening (5.4% × 0.16 = 0.86%).…”
mentioning
confidence: 99%
“…However, across groups, changes in self-monitoring were positively associated with PA increases as predicted by SCT and demonstrated in other studies. [20][21][22] The lack of increased social support among FITNET intervention participants may partially explain why no improvements in self-efficacy or self-monitoring were found in the FITNET intervention group relative to the self-help comparison group. The lack of FITNET intervention effects on self-monitoring could be due to both groups receiving a pedometer, FITNET intervention participants more accurately reporting their selfmonitoring behaviors (since they accessed the self-monitoring website), and/or self-help comparison group participants possibly over-reporting self-monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy, self-regulation, and environmental factors (e.g., social support) are key determinants of behavior described by SCT that have been targeted in several PA interventions. [19][20][21][22] In the context of PA, SCT suggests that a supportive environment may enhance individuals' self-efficacy (i.e., confidence in one's ability to perform exercise and to overcome barriers to exercise in specific settings) and in turn promote self-regulation (i.e., skills for personal regulation of goalsetting, planning, and self-monitoring) to effect behavior change.…”
mentioning
confidence: 99%